Enhancing professional communication through generative AI and multimodal literacy - Hamizah, Zahari; Siti Ainun Jariyah, Hassan; Noor Raha, Mohd Radzuan (Infrastructure University Kuala Lumpur, 2025)
This action research explores the use of Generative Artificial Intelligence (AI) in the English for Professional Communication course through an approach called V.I.P.: Visualising Interview Professionalism through Generative AI. Conducted among Diploma students at a Malaysian technical university, the study aimed to enhance students’ understanding of professional image and appropriate attire for mock job interviews. This is an area where Diploma students often demonstrate lower readiness compared to Degree-level learners. Grounded in Belshaw’s Digital Literacy Framework (2014) and Kress’s Multimodal Learning Theory (2010), the activity required students to generate AI images of themselves in professional attire and reflect on their choices through multimodal representations. Thematic analysis of students’ reflections revealed three key subthemes: (1) Conscious Construction of Professional Self, (2) Linking Attire to Academic and Career Identity, and (3) Reflection on Digital and Visual Literacy Development. Findings indicate that AI-assisted reflective tasks fostered students’ self-awareness, creativity, and understanding of professional expectations. Nevertheless, the study was constrained by a short implementation period and by varying levels of students’ digital literacy, which influenced the consistency of engagement and output quality. Despite these limitations, the findings demonstrate the pedagogical potential of Generative AI in enhancing reflective and multimodal learning, supporting educators in nurturing digitally literate and professionally prepared graduates. Keywords: generative AI, digital literacy, multimodal learning, ESP, reflective practice